"Fitness and Fatness" in Children and Adolescents: An Italian Cross-Sectional Study - Matteo Vandoni; Valeria Calcaterra; Vittoria Carnevale Pellino; Annalisa De Silvestri; Luca Marin; Gian Vincenzo Zuccotti; Valeria Tranfaglia; Matteo Giuriato; Roberto Codella; Nicola Lovecchio (MDPI AG, 2021)
Children with obesity tend to have lower level of physical activity compared to non-obese peers. In fact, sedentary behaviors are prevalent in obese children causing difficulties to perform motor tasks and engaging in sport activities. This, in turn, has direct repercussions on adiposity and related comorbidities. The aim of the study was to investigate several components of fitness and their relationship with the degree of fatness in children. We considered 485 Italian schoolchildren (9.5 ± 1.12 years). BMI and prediction modelling outputs of fat mass were employed as markers of body fatness. Physical fitness (PF) was assessed by the 9-item test battery (explosive power, leg muscle power, arm muscle power, upper body power, coordination, agility, speed and endurance). Differences between groups in the PF tests (p < 0.05) were noted. A similar pattern was reflected in both genders. The relationship between anthropometrics' characteristics and PF tests showed that weight and fat mass had a high level of correlation with different PF tests. Our findings highlight the importance of investigating the degree of fatness in relation with different components of fitness, in children and adolescents. This combination of proxies may cover an unexpectedly helpful screening of the youth population, for both health and performance.